AN ANALYSIS OF TEACHER CHALLENGES IN TEACHING ENGLISH AT SMAN 2 BANDA ACEH - Nur Amalia; Regina Rahmi; Mulyani; Eni Andriani (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to identify the difficulties of English teachers at SMAN 2 Banda Aceh encounter, the causes that contribute to those difficulties, and the strategies the teachers employ to overcome those difficulties. A qualitativedescriptive methodology was employed in this investigation. Researchers employed observation sheets and interviews to gather data for this investigation. The researchers discovered various difficulties for English teachers at SMAN 2 Banda Aceh based on the data collection results. Managing pupils presents several difficulties. The obstacles include students' lack of enthusiasm for learning English, ignorance of the fundamentals of English classes, using one's native tongue while learning English, and students' lack of self-confidence